2019
DOI: 10.1093/tbm/ibz114
|View full text |Cite
|
Sign up to set email alerts
|

The development and use of an assessment tool to capture changes in the food pantry nutrition environment and system of food distribution

Abstract: The MyChoice Scorecard assesses the food pantry environment, including client-choice, and can be used by community professionals to document and facilitate meaningful change in pantries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It showed that there was no compensatory change in SSB sales in other stores. The food pantry‐based study focused on improving the availability of healthy foods by supporting and educating food pantry managers 27 . Food environment scores in participating pantries improved significantly compared with those for non‐participating stores, but impacts on consumers were not evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It showed that there was no compensatory change in SSB sales in other stores. The food pantry‐based study focused on improving the availability of healthy foods by supporting and educating food pantry managers 27 . Food environment scores in participating pantries improved significantly compared with those for non‐participating stores, but impacts on consumers were not evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the 21 studies did not report on rural communities experiencing significant disadvantage, 22‐25 and seven of the 21 studies only reported food environment change (ie, not change in consumer behaviour such as dietary intake or purchasing). 23,25‐30 A summary of included studies is provided in , Table 1.2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The Voices for Food project showed a significant increase in CNE changes among 12 pantries provided coaching by Extension staff, in comparison with control pantries provided resources but no coaching. 32 However, no details about the specific CNE changes adopted by pantries in these studies were reported. A recent pilot study of the SuperShelf intervention is 1 exception, describing implementation fidelity of CNE changes in 2 pantries that were provided coaching and support by Extension staff for 2 −4 months.…”
Section: Discussionmentioning
confidence: 99%